Dosis de Aplicación del Cube (Lonchocarpus utilis A.C.Smith). en el control del Gusano Cogollero Spodoptera frugiperda (J .E Smith) en el cultivo de Maíz (Zea mays L.) - Ruiz Beteta, Rosmery (1995)
This work was carried out between the months of August to October 1993 in the sector Ahuashiyacu, District Band Shilcayo the 1st province and department of San Martin, located 76 "12 'west longitude, 6" 22' south latitude and an altitude of 330 meters above sea level. the percentage of dead larvae armyworm Spodoptera frugiperda (Smith J. E) according applied concentrations was evaluated. Corn planting was performed with a distance of 0.80 cm and 0.80 cm between blow between the lines. Healthy plants were infested with larvae of the armyworm (one larva per plant), achieving uniform population of each treatment and repetici6n, product application for cube powder in different concentrations. According to the results of statistical analysis highly significant differences in the mortality of FAW found. Best result was with the concentration of 90 g. the farmer recommends using 3 kg of powder cube for one hectare plantation.